A Target Model for Social Justice Supervision - Sara E Ellison; Paul Tierney; Margaret Taylor (Teaching and Supervision in Counseling, 2024)
Addressing social justice in supervision is essential to dismantling systemic oppression and infusing social justice practices into the profession of counseling. Despite the importance of social justice to the training and development of novice counselors, few models exist in the professional literature to guide supervisors wishing to integrate these essential competencies. This article proposes a simple, structured Target Model for Social Justice Supervision utilizing the roles of Bernard’s Discrimination Model to focus on self-awareness, client and supervisee worldview, the counseling and supervision relationship, social justice interventions, and evaluation procedures. Specific goals, strategies, interventions, and the application of the model are discussed.
Keywords: social justice; clinical supervision; Discrimination Model; Multicultural and Social Justice Counseling Competencies; counselor training